Intake and exhaust ports flow investigation of 4-stroke SI engine - Mohammad Amin, Mohamed (2010)
This project is focused to investigate the test rate characteristics through the intake and exhaust ports of four-stroke single cylinder engine (Modenas Kriss 110cc) by using flowbench machine. This investigation is to measure the volumetric flow rate into intake and exhaust valve ports at various valve lift by using flowbench machine. The flow characteristic through the intake and exhaust valves at various engine vacuum conditions must also be investigate. This investigation is done by disassembling the engine in order to obtain the cylinder head. That cylinder head engine is mated to an adapter as replacement for the cylinder block engine. After that, the adapter and cylinder head will be mounted on flow bench machine. The test bench is prepared to vary the intake and exhaust valves lift to be mounted on the flow bench and then the flow test is conducted at various test pressures. A variety of valve opening was measured by using dial gauge and various test pressure is measured at Flowbench setting. The flow bench can read correction test flow and flow velocity. Flow will increase directly proportional to the valve lift. At the highest test pressure, flow is the greatest.